PENGEMBANGAN MODUL DIGITAL ELEKTRONIKA DASAR UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN TEKNOLOGI DASAR OTOMOTIF DI SMK MUHAMMADIYAH 3 YOGYAKARTA - Robertus Armando Godat; setuju (Program Studi Pendidikan Vokasional Teknik Mesin, Universitas Sarjanawiyata Tamansiswa, 2024)
This study aims to determine the feasibility of a good and quality basic electronic digital module. This research is development research. The research model has 4 stages in the research, namely define, design, develop and desseminate. Educational materials (learning modules) for Basic Automotive Technology subjects were validated by 2 material experts and 2 media experts, then tested on 42 students of class X majoring in Light Vehicle Engineering at Vocational High School (SMK) Muhammadiyah 3 Yogyakarta. Collecting data using a 4-preference Likert scale questionnaire/questionnaire. The results of the module expert assessment are 3.09 from the optimal score of 4 so that they are listed in the